PERAN GURU BIMBINGAN DAN KONSELING PADA IMPLEMENTASI KURIKULUM MERDEKA - Anisah Azzahra; Mudaim; Hadi Pranoto (Counseling Milenial (CM), 2026)
The purpose of this research is to describe the role of guidance and counseling teachers in the implementation of the independent curriculum at SMP Negeri 1 Punggur, Central Lampung. Then explain what the roles and challenges are in the implementation of the independent curriculum and how the efforts made by guidance and counseling teachers in overcoming the challenges of the independent curriculum at SMP Negeri 1 Punggur. The research approach used is qualitative research with a narrative research type. With qualitative research, it is possible to obtain complete and accurate data. The methods used in data collection are field observations and interviews. Based on the research results that have been carried out regarding the role of guidance and counseling teachers in the implementation of the independent curriculum, it can be concluded that the role of guidance and counseling teachers in the independent curriculum includes being a motivator, agent of change and prevention, facilitator, counselor, career development, consultant, assessor, and collaborating with the school. The challenges faced by guidance and counseling teachers include adapting to technology, having creativity and innovation in learning methods, increased workload, and limited human resources. Efforts made to overcome these challenges include motivating themselves, attending training and competency development activities, collaborating with various related parties, and gaining support from the school.